Manufacturing Epidemics: The Role of Global Producers in Increased Consumption of Unhealthy Commodities Including Processed Foods, Alcohol, and Tobacco - Stuckler, David; McKee, Martin; Ebrahim, Shah; Basu, Sanjay (PLoS medicine, 2012)
In an article that forms part of the PLoS Medicine series on Big Food, David Stuckler and colleagues report that unhealthy packaged foods are being consumed rapidly in low- and middle-income countries, consistent with rapid expansion of multinational food companies into emerging markets and fueling obesity and chronic disease epidemics.